Research Progress on Lignocellulosic Biomass Degradation Catalyzed by Enzymatic Nanomaterials. Issue 18 (9th August 2022) - Luo, Hangyu; Liu, Xiaofang; Yu, Dayong; Yuan, Junfa; Tan, Jinyu; Li, Hu
Abstract: Lignocellulose biomass (LCB) has extensive applications in many fields such as bioenergy, food, medicines, and raw materials for producing value‐added products. One of the keys to efficient utilization of LCB is to obtain directly available oligo‐ and monomers (e. g., glucose). With the characteristics of easy recovery and separation, high efficiency, economy, and environmental protection, immobilized enzymes have been developed as heterogeneous catalysts to degrade LCB effectively. In this review, applications and mechanisms of LCB‐degrading enzymes are discussed, and the nanomaterials and methods used to immobilize enzymes are also discussed. Finally, the research progress of lignocellulose biodegradation catalyzed by nano‐enzymes was discussed. Abstract : This review introduces hydrolases, immobilized materials and immobilization methods for biodegradation of lignocellulosic biomass, and the roles/mechanisms of nano‐immobilized hydrolases in the conversion of lignocellulose to simple sugars.